A developmental study of the Visayan Daily Star through an index 1982-1996 - De Guzman, Ma. Girlie E. (1998)
This study used the document analysis method of research which requires thorough scanning and reading of all issues of the Visayan Daily Star from 1982 to 1996 available at the college library of University of St. La Salle-Bacolod, Office of the Publisher and Microfiche Department of Rizal Library, Ateneo de Manila University. The specific objectives of the study are: (1) to determine the kinds of articles found in the newspaper, (2) to identify the scope and subject/s of the newspaper, (3) to know the trends in its development and changes in its thrusts; and (4) to determine whether the newspaper contributes to the furtherance of research on and the local history of Negros Occidental. The major findings of the study include: (1) the top newspaper articles published from 1982 to 1996 were about the sugar industry, insurgency, labor, economics, government and politics, sports, church, agrarian reform, agriculture and education, (2) the Visayan Daily Star is free from biases, has a fair and balanced reporting and covers all aspects of the events that are happening in the community, (3) the focus of the paper is more on local issues rather than national and international issues, (4) literary articles include only poems and essays which are quite few; (5) the Visayan Daily Star is going global and is accessed through the internet; (6) articles such as history of municipalities, towns and cities of the province or region; biographies of prominent persons; special features such as Masskara articles that form part of the history and found only in the newspaper; (7) the Visayan Daily Star is a forum of opinion to many and an eye opener through the letters, comments, opinions of the readers; (8) the advertisement and classified ads contributed to the economy and development of Bacolod City and the Negros Occidental. The Visayan Daily Star has been a source of information to almost all the residents. Based on the above findings, the Star has attained the objective of serving the community.